Factors associated with morbidity and mortality of Cholera and Diarrhorea in Poverty Driven rural villages of Beluran Health District - Thant Zin (Universiti Malaysia Sabah, 2012)
Diarrhoeal and cholera diseases kill on estimated 2.5 million people globally every year; the majority is, under five children. In Sabah state, chlorea is sporadic occurrence. Seven cholera cases reported from January to October 2011 in Beluran district. In 2012, a research team from Universiti Malaysia Sabah was carried out the study to identify relationship between environmental factors (water, sanitation and hygiene) and choler and diarrhea in the selected affected villages. This study is population base cross sectional study in the affected villages of Beluran district. All households in three targeted villages were surveyed. SPSS 21 has been used for statistical analyses.